2022
DOI: 10.1177/21582440221111102
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Organizational Cynicism in School Effectiveness?

Abstract: Human resources are frequently emphasized as being critical to the school social system’s survival. This study examined the effects of teachers’ negative attitudes toward the organization for which they work at the level of school effectiveness. The study sought to determine how negative attitudes of secondary school teachers toward their schools harmed school effectiveness in one of Turkey’s eastern provinces. The analyses revealed that organizational cynicism may reduce perceived school effectiveness by redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
3
0
2
Order By: Relevance
“…OC had a statistically significant negative effect on PSE, as well as on IDM. IDM showed a statistically significant positive effect on PSE [53]. Gülbahar [54] (p. 15) reported that "the perceived supervisor support among teachers is positive on school effectiveness perception, engagement to work and job satisfaction and negative on organizational cynic attitude".…”
Section: Teacher Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…OC had a statistically significant negative effect on PSE, as well as on IDM. IDM showed a statistically significant positive effect on PSE [53]. Gülbahar [54] (p. 15) reported that "the perceived supervisor support among teachers is positive on school effectiveness perception, engagement to work and job satisfaction and negative on organizational cynic attitude".…”
Section: Teacher Effectivenessmentioning
confidence: 99%
“…It is therefore very important to increase the level of participation of teachers in decisions [52]. Yıldırım [53] claimed that organizational cynicism (OC) indirectly affects perceived school effectiveness (PSE) through involvement in the decision-making (IDM) process and may reduce perceived school effectiveness by reducing teachers' participation in school decision making. OC had a statistically significant negative effect on PSE, as well as on IDM.…”
Section: Teacher Effectivenessmentioning
confidence: 99%
“…În cercetarea realizată de I. Yildirim [10] într-o provincie din Turcia au fost analizate implicațiile atitudinilor cinice ale cadrelor didactice asupra eficienței școlii. Studiul constată că cinismul organizațional afectează participarea cadrelor didactice în procesele decizionale din cadrul instituției.…”
Section: Tendinţe Recente îN Cercetarea Cinismulului îN Instituţiile ...unclassified
“…Dimpotrivă, cadrele didactice se angajează în conduite ce presupun critici acerbe la adresa instituției și se implică mai puțin în adoptarea unor tehnologii noi sau orice alte inițiative, în afara fișei de post, ce ar spori performanța. Cadrele didactice care au dezvoltat atitudini cinice față de instituția școlară, scrie I. Yildirim [10], nu se implică în rezolvarea proble-melor instituției, nu caută soluții adecvate pentru rezolvarea acestor probleme și nu sunt interesați de creșterea eficienței școlii în care sunt angajați.…”
Section: Tendinţe Recente îN Cercetarea Cinismulului îN Instituţiile ...unclassified
“…For these various reasons, OCO and SDE have a positive connection or relationship. Finally, concerning positive workloads in OCO as a sub-construct, it will lead to the formation of a relationship with student learning strategies because conceptually, the teacher's achievements are in the form of being anti-procrastination, sincerity and a happy state when carrying out various tasks is the primary concern for achieving SDE (Lee & Shute, 2010;Yıldırım, 2022;Yulianti et al, 2019). It is also reinforced by expert opinion, which states that antiprocrastination activities and a pleasant working atmosphere can help achieve work results toward customer satisfaction (Metin et al, 2018;Sallis, 2014).…”
Section: Relationship Between Organizational Culture Openness and Sch...mentioning
confidence: 99%